SOCIAL TRANSFORMATION IN AGRARIAN SOCIETY TOWARDS AN INDUSTRIAL SOCIETY - Afrilian, Alita Harya; Subachtiar, Aris (LPPM Universitas Bina Bangsa, 2025)
The aim of this research is to describe the social transformation in an agrarian society towards an industrial society using a literature approach. The method used is a descriptive method with a literature approach using 50 journals, both international and national journals. Before publishing this paper, it was discussed by the lecturer concerned and also friends, the aim of which was to discuss and correct if there was something wrong. After it has been repaired and is in accordance with the regulations, this paper is published. The aim of this paper is to increase knowledge and become a learning medium in the future. Based on the results of the literature, it can be concluded that social transformation in an agrarian society towards an industrial society is the first, social change in society is something that often occurs, so there are many consequences of the change itself. Second, an agrarian society is a society that always relies on natural products, while an industrial society is a society that is technologically literate. Third, this transformation causes many impacts, one of which is urbanization. The recommendation of this research is that agrarian society must adapt as much as possible to the times that continue to develop, so that society will grow more prosperous in all aspects, be it economic, social, and so on. An industrial society must be able to balance industry and environmental concerns, so that nature will remain green.